(untitled) (Journal of Academic Research, 2024)
The study aimed to determine the degree of awareness of primary school teachers in the city of Bani Walid regarding students with academic learning difficulties, and to know the significance of the differences between academic qualifications and teaching experience. The researcher relied on the descriptive and analytical approach, and on a scale of the degree of awareness of primary school teachers of academic learning difficulties, which was prepared from According to Razia Gharbi (2018), the study sample consisted of (118) female teachers. The study concluded that the degree of teachers’ awareness of students with learning difficulties is low, and that there are no statistically significant differences between the average grades of the sample members depending on the variable of teaching experience or qualification. The researcher recommended that the Ministry of Education pay attention to pre-service teacher preparation programs and encourage them, in order to raise the level of teachers’ knowledge of this problem. The researcher recommended the need for the Ministry of Education to pay attention to pre-service and in-service teacher preparation programs, in order to raise the level of teachers’ knowledge of students with learning difficulties.